The Creation of Human in Qur’an - Saifuddin, Hadid Humaid; Ibrahim, Muhammad Fikri; Permana, Yana; Yusron, Muhammad Agus (Institut Agama Islam Persis Bandung, 2023)
The focus of this article is on the depiction of the creation of mankind in the Qur'an, and its subsequent interpretation. The aim of this research is to examine scientific verses related to human creation as presented in the Qur'an. This study employs a qualitative comparative method and utilizes a literature review approach, with data sourced from the book